Identification of the overexpressed genes in hepatocellular carcinoma using Expressed Sequence Tags - Sim-Hui, Tee (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/